Tinjauan Sistem Informasi Akuntansi dalam Meningkatkan Kinerja Organisasi dan Meminaliris Eror - Isma Dina; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of accounting information systems in enhancing organizational performance and minimizing errors through a conceptual-critical approach based on a systematic literature review. The analysis integrates perspectives of accounting information systems as socio-technical systems and internal control frameworks to explore mechanisms linking system quality, organizational processes, and error reduction. The findings indicate that accounting information systems improve decision-making quality by providing accurate, timely, and relevant information, while strengthening internal control through preventive and detective mechanisms such as validation procedures, audit trails, and access control. The effectiveness of these systems is influenced by the alignment between technological infrastructure, user competence, and organizational context. The study also highlights that errors originate not only from human factors but also from system design limitations, requiring integrated control strategies. This study provides a conceptual foundation for future empirical research on multidimensional system effectiveness.